Pelatihan Pembuatan Video Pembelajaran Interaktif dan Film Edukasi SMKN1 Simpang Katis - Ade Septryanti; Hilyah Magdalena; Hadi Santoso; Hensceh Gunawan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The objectives of holding Community Service Program activities for teachers in SMK are: (1) To provide education to Information Technology teachers at SMK in the Central Bangka Regency area about training in making learning videos and educational films to assist the teaching and learning process; (2) Improving the creativity of Information Technology Vocational Schools in the Central Bangka Regency area about compiling the stages of making learning videos and educational films. This community service is carried out using training and mentoring for SMK Information Technology teachers to prepare learning materials both online and offline. The training for making learning videos and educational films was attended by teachers of Information Technology Vocational Schools in the Central Bangka Regency area. Community service program activities were held at the Computer Laboratory of SMKN 1 Simpang Katis involving 3 lecturers and 1 student. The form of community service activities carried out in the form of training and mentoring for teachers. The output of this community service activity is that teachers can make learning videos and educational films both online and offline. The material provided in the training is carried out offline with material exposure according to the revised K-13 curriculum.